Identification of Prognosis Biomarkers for High-Grade Serous Ovarian Cancer Based on Stemness - Wang, Zhihang; Yang, Lili; Huang, Zhenyu; Li, Xuan; Xiao, Juan; Qu, Yinwei; Huang, Lan; Wang, Yan (Frontiers in Genetics, 2022)
Ovarian cancer is a highly malignant tumor threatening women’s health. Ovarian cancer patients have the clinical characteristics of drug resistance and high recurrence rate after postoperative chemotherapy. However, there is currently no effective early screening method and perfect treatment strategy. Cancer stem cells (CSCs) are self-renewing cells in tumor tissues, which have the potential of multidirectional differentiation and heterogeneous tumor cells generation, and are the main cause for drug resistance, recurrence and metastasis of tumor. Therefore, identifying cancer stem cells and screening gene markers related to prognosis will help solve the problem of drug resistance and recurrence of ovarian cancer. In this paper, high-grade serous ovarian cancer (HGSOC) is studied, which is the most common histological subtype of ovarian cancer. Through integrating bulk RNA-Seq data of cancer samples from TCGA, UCSC Xena and single cell RNA-Seq data from GEO of HGSOC, and performing a series of computational analyses on them, we explore stem cell populations in ovarian cancer, identify stemness markers and survival-related markers, and provide potential treatment recommendation. As a result, 171 key genes for capturing stem cell characteristics are screened and one vital tumor stem cell subpopulation is identified. Through the analysis of this study, the obtain key genes COL1A1, COL1A2, MT-CYB, RPS18, RPL3, RPL13, RPS2, RPL18A, HMOX1, SQSTM1, RPL24, EEF1A1 has been reported to have a very close relationship with cancer, so these genes have the potential to be used as prognostic biomarkers for ovarian cancer. However, NACA, RPL10A, CCT5 and PAPPA have not been reported to be closely associated with cancer, so they can provide good markers for experimental researchers to conduct experimental research.